8: Carbon taxes - Baranzini, Andrea (Edward Elgar Publishing, 2023)
A carbon tax is a surcharge on a fuel, product, or service, in proportion to the quantity of carbon embodied or emitted, thereby providing financial incentives to abate emissions. Together with emissions trading systems, carbon taxes are the most widespread economic instruments dedicated to curb CO2 emissions and ultimately mitigate climate change. A central characteristic of carbon taxes is cost-effectiveness: a given amount of emission reductions is achieved at the lowest possible cost. However, carbon taxes raise distributional concerns and face acceptability issues. This entry discusses the functioning of carbon taxes and their main properties.